Exonic variants of GPIHBP1 gene in Thai subjects with severe hypertriglyceridemia - Plengpanich, Wanee; Muanpetch, Suwanna; Charoen, Supannika; Kiateprungvej, Arunrat; Khovidhunkit, Weerapan (Chulalongkorn Medical Journal, 2023)
Background: Hypertriglyceridemia (HTG) is one of the risk factors for cardiovascular disease and acute pancreatitis. It is associated with genetic variations in various genes involved in triglyceride metabolism. Glycosylphosphatidylinositol-anchored high-density lipoprotein-binding protein 1 (GPIHBP1) encodes a membrane protein involved in an intravascular triglyceride hydrolysis. Objective: The purpose of this study was to examine the genetic variants in the exons of GPIHBP1 gene in Thai subjects with severe HTG. Methods: All 4 exons of the GPIHBP1 gene were sequenced in 101 Thai subjects with severe HTG. All subjects had triglyceride levels e” 10 mmol/L or 886 mg/dL. Subjects with normolipidemia (n = 111) were used as controls. Results: The allele frequency of the common p.Cys14Phe variant (rs11538389) in control group was higher than in severe HTG group (0.523 vs. 0.386, P = 0.11). Interestingly, 2 rare missense variants were identified in 3 HTG patients. A homozygous p.Ser107Cys (rs587777643) was found in 1 patient and a heterozygous p.Arg16Gln (rs748509621) was found in 2 patients. These two rare variants were not observed in the normolipidemic controls. Conclusion: Our study demonstrated that p.Ser107Cys and p.Arg16Gln variants were exclusively found in HTG patients. The finding suggested that these 2 variations in GPIHBP1 gene might be a rare genetic cause of severe HTG among Thai population.